On products of self-small abelian groups - DVOŘÁK, Josef (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
An abelian group A is called self-small if direct sums of copies of A commute with the covariant Hom(A;-) functor. The paper presents an elementary example of a non-self-small countable product of self-small abelian groups without non-zero homomorphisms between different ones. A criterion of self-smallness of a finite product of modules is given. Mathematics Subject Classification (2010): 16D10, 16S50, 16D70.